Pengaruh Bahasa Pemrograman Scratch pada Mata Pelajaran Informatika untuk Meningkatkan Self Efficacy Siswa Kelas VIII di SMP 8 Padang - Azaharani, Meissy Anggun; Hidayati, Abna; Rayendra, Rayendra; Rahmayanti, Elsa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The importance of learning Informatics is not only limited to mastering techniques and practical skills in technology development, but also in forming students' self-efficacy or self-confidence in overcoming challenges and solving problems in the digital world. This study aims to analyze the influence of Scratch programming language on informatics subjects to improve the self-efficacy of grade VIII students at SMP 8 Padang. This type of research is quantitative research with an experimental method. The design used in this research is a Quasi Experimental Design in the form of a Nonequivalent Control Group Design. The data collection technique used is a Likert scale questionnaire. The experimental group used the scratch programming language with a total of 32 students, and the control group used the blookly programming language with a total of 32 students. For hypothesis testing, this study uses t-test statistics with a significant level of 5% (= 0.05) and N-Gain test. The results of the study showed that the use of scratch programming language influenced the self-efficacy of grade VIII students of SMP 8 Padang with a significance value of 0.001. This means a significant t-value (p = 0.001 < 0.005). In the N-Gain analysis, the experimental class experienced an increase in self-efficacy score of 0.54 (medium category), while the control class only 0.07 (low category)